Changes during fasting in the activity of a specific lysosomal proteinase, fructose-1,6-bisphosphatase converting enzyme. - Melloni, E (1981)
Three lysosomal proteinases capable of catalyzing a limited modification of the gluconeogenic enzyme fructose-1,6-bisphosphatase (D-fructose-1,6-bisphosphate 1-phosphohydrolase, EC 3.1.3.11) have been purified from extracts of rabbit liver lysosomes. These have been designated "converting enzymes I, II, and III," respectively, based on the order of their elution from Ultrogel AcA34. The predominant form in lysosomes from livers of fed rabbits is converting enzyme III which has been identified as a mixture of cathepsins B and L. Fasting induces a 4- to 5-fold increase in the activity of converting enzyme II; in the livers of 96-hr-fasted rabbits, this form accounts for more than 70% of the total converting enzyme activity. The increase is largely in that fraction of converting enzyme II associated with lysosomal membranes; this increase is also seen in the activity expressed by intact lysosomes. The activity of intact lysosomes is not due to their increased fragility because other lysosomal enzyme activities remain latent. The effect of fasting on the activity of converting enzyme II is selective and greatly exceeds the 2-fold increase observed for other lysosomal enzymes.